Gestión administrativa y su incidencia en el desarrollo institucional - Gualavisí Farinango, Adriana Mishelle (2019)
The present case study is focused on the analysis of administrative management and institutional development, the investigation is carried out in the Ernesto Alban Mosquera Educational Unit of the city of Santo Domingo de los Tsachilas, where important weaknesses have been observed as for the administrative functions performed by the employees of this entity. The objective of the research work is to analyze the incidence of administrative management in institutional development. The type of research is descriptive, by virtue of the description that is made of the variables of the research topic, the method used is the inductive one, since it is based on the analysis of particular situations observed in the institution, to reach generalized conclusions regarding the subject; The relevant technique for this work is the interview which has been directed to administrative staff of the Educational Unit and to ten student representatives. The results obtained reflect that the collaborators have important administrative weaknesses, which has directly influenced the development of the institution; These weaknesses have been caused by the lack of training for employees, the conclusions reached are that professionals do not use planning tools such as the POA and PEDI